Pd Doped on TCH@SBA-15 Nanocomposites: Fabrication and Application as a New Organometallic Catalyst in the Three-Component Synthesis of N-Benzo-imidazo- or -thiazole-1,3-thiazolidinones - Kalhor, Mehdi; Dadras, Akbar (Frontiers in Chemistry, 2021)
In this study, Pd(II)/TCH@SBA-15 nanocomposites were synthesized by the grafting of 3-chloropropyltriethoxysilane and thiocarbohydrazide on SBA-15 and subsequent deposition of palladium acetates through the ligand–metal coordination method. The structure and morphology of this nanoporous nanocomposite was thoroughly identified by Fourier transform infrared spectroscopy, field emission scanning electron microscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction, thermogravimetric analysis, atomic absorption spectroscopy, and Brunauer–Emmett–Teller instrumental analyses. Furthermore, the catalytic activity of this nanocomposite was investigated in the three-component synthesis of 3-benzimidazolyl or benzothiazoleyl-1,3-thiazolidin-4-ones via a reaction of 2-aminobenzimidazole or 2-aminobenzothiazole, aromatic aldehydes, and thioglycolic acid in an acetone–H2O mixture under green conditions. The Pd/TCH@SBA-15 nanocatalyst is demonstrated to exhibit a high catalyzing activity in the three-component reaction of the synthesis of N-heterocyclic thiazolidinones with good to excellent yields. One of the advantages of the suggested method is the direct application of the thiocarbohydrazide ligand to stabilize Pd nanoparticles through formation of a stable ring complex without creating an additional Schiff base step. Moreover, this organometallic nanocatalyst can be recycled several times with no notable leaching or loss of performance.